E-Governance in Palestine and the MENA Region - Marah An-najjar; Menna AlKhayyat (My University, 2022)
There are always a large number of inquiries and complaints that reach the municipality of Nablus daily, which are submitted by citizens, and because of the huge numbers of them and other obstacles such as the lack of staff of the Complaint department or the use of traditional methods, responding to all complaints has become very difficult. In addition, responding to inquiries takes a long time, and as an inevitable result has led to the citizens' lack of confidence in the municipality and their belief in the municipality's inability to prioritize problems. The residents of Nablus city in general, and the beneficiaries of its municipal services in particular, suffer from a lack of response to their complaints or requests submitted to the municipality. The municipality employees suffer from the pressure imposed on them due to the number of phone calls from citizens whose want to submit a complaint or a specific request. On the other hand, their use of traditional ways of dealing the complaints reduces their effectiveness and the chances of responding to all citizens’ complaints and requests. With the problem of citizen dissatisfaction because of poor communication with the municipality, a new obstacle has emerged, which is not reaching the problem until it aggravates, thus causes more time and financial loses and may lead to other problems. Moreover, one of the problems facing the municipality is the problem of citizens' lack of awareness of the municipality's way of work and its policies and also how to submit complaints. In addition to the lack of patience and understanding to prioritize problems, which restricts the work of the municipality. Taking on consideration all of the above, the need of citizens and municipality employees to have a unique application that facilitates the process of submitting complaints or requests and sorting them in order to save time and efforts increases with the increase in the population of the city and with the evolution of life in its various fields. In this project, we afford help for Nablus citizens who surely have constant complaints or mobile application facilitated and built demands from the municipality by providing a customized based on the human centered design approach. The new methods provided by the mobile application will improve the quality of service provided to the user which is done by determining the frequency of complaints submitted based on a system that defines them by keywords and quality of filtering to employees by filtering, redirecting complaints to the specific department all automatically using artificial intelligence without the need for employee’s interaction.